THE EFFECTIVENESS OF CONTEXTUAL LEARNING METHODS AND TECHNOLOGY USE IN TEACHING ISLAMIC RELIGIOUS EDUCATION IN VOCATIONAL HIGH SCHOOLS - Dedi Rosyidi; Muharor (Al-Masail: Journal of Islamic Studies, 2023)
This study aims to evaluate the effectiveness of contextual learning methods and the use of technology in enhancing students' knowledge and motivation in teaching Islamic Religious Education (PAI) in Vocational High Schools (SMK). The respondents of this study were 60 eleventh-grade students of SMKN 2 Depok Sleman, divided into two groups: an experimental group of 30 students using contextual learning methods and technology, and a control group of 30 students using conventional methods. The research method employed was quasi-experimental. Data were collected through pre-tests and post-tests to measure students' knowledge and questionnaires to evaluate their learning motivation. The results showed that the experimental group experienced a significant increase in both knowledge scores and motivation compared to the control group. The average post-test score increase for the experimental group was 20 points, while the control group only increased by 6 points. The novelty of this research lies in the integration of contextual learning and technology in teaching PAI, which has been minimally explored in previous literature. The global benefit of this research is to provide insights and models for developing innovative teaching methods that can be applied to various subjects and educational contexts worldwide, creating more relevant and engaging learning environments for students.